PEMBUATAN SABUN DALAM BENTUK POLIOL DARI MINYAK BIJI KELOR (Moringa oleifera) - Sihombing, Eka Putri Jayanthy; Tarigan, Daniel; Sitorus, Saibun (JURNAL ATOMIK, 2016)
Polyol compounds obtained by epoxidation dan hydroxylation, the results obtained with the reaction yield of 69.23%. Potassium soap mixture in the form of a polyol obtained by saponification polyol with Potassium Hydroxide with a yield of 70.36%. Polyol and potassium soap in the form of a polyol mixture was analyzed by FT-IR spectrophotometer.Respectively iodine from moringa seed oil and polyol are 107.3769 mg I / gram of oil and 4.6755 mg I / gram of oil. HLB of fatty acid potassium soap of moringa seed oil and potassium soap in the form of a mixture of polyol is determined by titration method and obtained HLB of fatty acid potassium soap of moringa seed oil amounted to 5,2178 while the potassium soap in the form of a polyol mixture of 8,4767. Free alkalinity of soap potassium mixture in the form of a polyol is 0.551%. Based on the stability and strength of the foam test, the concentration of potassium soap mixture in the form polyols having the most excellent foam stability is 1% and which has the best strength is 1%.Keywords: moringa seed oil, epoxidation, polyol, saponification